Analisis Kritis Terhadap Penegakan Hukum Dalam Penanganan Kejahatan Siber Pada Kasus Data Breach Dalam Perspektif Hukum Pidana Indonesia - Raden Andhitya; Jamaludin Umam (CV Rewang Rencang, 2025)
The presence of globalization has a rapid impact on technological progress. In addition to positive impacts, these advancements also have negative impacts, such as the emergence of misuse and technology-based crimes such as data breaches. In this case, Indonesia actually has a legal framework for further handling related to action ii. However, its implementation often faces challenges and obstacles. This research aims to analyze and legal framework and handling of data breach crimes and evaluation of the criminal justice system for these crimes in Indonesia. This research is a qualitative research with descriptive analytical method based on literature study data. The results of this study concluded that Indonesia has created a normative legal framework in dealing with the threat of data breach crimes, namely the ITE Law and the PDP Law. In its implementation, it appears to face various challenges. The main challenges include difficulties in collecting digital evidence, limited understanding of legal officers, and lack of coordination between institutions.